Food, consumers and food industry - Fuller, Gordon W. (CRC Press LLC, 2011)
During the past, there have been many changes in food availability, production and selection around the world. These changes, such as genetically modified foods, raise questions about their long-range implications. How will they affect the worldwide economics and management of agriculture? food legislation? the environment? the determination of food safety and quality? nutrition and health? Food, Consumers, and the Food Industry: Catastrophe or Opportunity? describes the major changes and answers the questions concerning them. It presents information that decision-makers in the field can utilize on such topics as:o Consumers and consumerismo Marketing and the marketplaceo Retailingo Nutrition and healtho Impact of new technologiesFood, Consumers, and the Food Industry encourages you to set aside the "truth" of science to consider how political, economic, social, and cultural institutions can work to avoid a possible crisis.